Studies on the purification of antihemophilic factor (factor VIII): II. Separation of partially purified antihemophilic factor by gel filtration of plasma - Ratnoff, Oscar D. (1969)
A high degree of purification of antihemophilic factor was achieved by filtration of chylomicronpoor human plasma through columns of agarose. The final product contained, on the average, 67 units of antihemophilic activity per mg of protein, and was 3360-fold purified compared with the filtered plasma. The molecular weight of antihemophilic factor appeared to be at least two million. Preparations separated by gel filtration were contaminated with appreciable amounts of plasma thromboplastin antecedent (PTA), and traces of Christmas factor and Hageman factor, but no detectable fibrinogen was present. Similar fractions of plasma prepared from the blood of patients with classic hemophilia, von Willebrand's disease, or a circulating anticoagulant directed against antihemophilic factor contained, on the average, somewhat less protein than normal plasma; whether this difference was significant is not yet known. The purified fractions were partially stabilized by the addition of 1% gelatin. Adaptation of the technique of gel filtration to purification of antihemophilic factor for clinical use remains to be explored.